Scientometrics: a tool for the insertion of Brazilian Dermatology in the world scientific production - Henrique Seiji Furukawa; Ana Clara Ladeira Cruz; Edileia Bagatin; Guilherme Sydow Nunes Bueno Brandão (Sociedade Brasileira de Dermatologia (SBD), 2022)
Introduction: The Brazilian scientific production in Dermatology in the international scenario was verified by scientometrics (Sociology segment on quantitative aspects of science). Objective: The insertion of Brazil in the international scientific production scenario can and should be conducted from a more strategic perspective, and it is necessary to observe the production of documents indexed in Scopus in the Dermatology area and related topics in a more detailed way. Methods: Through exploratory, inductive, quantitative, and qualitative research on the Scopus platform - a digital platform comprising more than 25 thousand scientific articles and analytical tools to extract results and trends in the field of research, it was possible to obtain quantitative data on Brazilian scientific production in General Dermatology and six prominent dermatoses. Results: It was possible to analyze and point out the most prominent dermatoses currently in the literature and the related authors, compare Brazilian data with those from other countries that stand out in the scientific literature in Dermatology, and elaborate and justify effective strategies for the international insertion of Brazilian Dermatology scientific production.